Self-assembled InGaAs/GaAs quantum dots - Sugawara, Mitsuru (Semiconductors and semimetals, 1999)
This volume is concerned with the crystal growth, optical properties, and optical device application of the self-formed quantum dot, which is one of the major current subjects in the semiconductor research field. The atom-like density of states in quantum dots is expected to drastically improve semiconductor laser performance, and to develop new optical devices. However, since the first theoretical prediction for its great possibilities was presented in 1982, due to the difficulty of their fabrication process. Recently, the advent of self-organized quantum dots has made it possible to apply the results in important optical devices, and further progress is expected in the near future. The authors, working for Fujitsu Laboratories, are leading this quantum-dot research field. In this volume, they describe the state of the art in the entire field, with particular emphasis on practical applications.